2016
DOI: 10.1037/apl0000039
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel perspective on faultlines: Differentiating the effects between group- and organizational-level faultlines.

Abstract: Integrating the literature on faultlines, conflict, and pay, we drew on the basic principles of multilevel theory and differentiated between group- and organizational-level faultlines to introduce a novel multilevel perspective on faultlines. Using multisource, multilevel data on 30 Major League Baseball (MLB) teams, we found that group-level faultlines were negatively associated with group performance, and that internally focused conflict exacerbated but externally focused conflict mitigated this effect. Orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 176 publications
(220 reference statements)
2
55
1
Order By: Relevance
“…Bezrukova et al. () recently proposed conflict as a moderator of the faultline–performance outcome and found evidence supporting their social identity arguments in a multilevel study of major league baseball teams. We argue and find evidence that conflict can moderate the faultline–performance relationship, offering opposite predictions, based on the CEM.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Bezrukova et al. () recently proposed conflict as a moderator of the faultline–performance outcome and found evidence supporting their social identity arguments in a multilevel study of major league baseball teams. We argue and find evidence that conflict can moderate the faultline–performance relationship, offering opposite predictions, based on the CEM.…”
Section: Discussionmentioning
confidence: 90%
“…The literature has generally shown that faultlines impede group performance as the emergence of subgroups can lead to ingroup–outgroup competition, restricted communication, and decreased information sharing (Bezrukova et al., ; Homan et al., ; Jehn & Bezrukova, ; Lau & Murnighan, ; Sawyer, Houlette, & Yeagley, ; Thatcher et al., ). In recent years, research on faultlines and subgroups has unpacked these basic relationships by uncovering a variety of faultline types, measures, mediators, moderators, and consequences (Bezrukova et al., , ; Shaw, ; Thatcher et al., ). As a full review of faultline theory is beyond the scope of this manuscript, we develop our argument for conflict as a moderator focusing on research about bridging faultlines, or lessening negative effects on group performance.…”
Section: Theory Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…We followed the approach of previous research on team diversity (e.g., Bezrukova, Spell, Caldwell, & Burger, 2016;Bishop Smith & Hou, 2015) and used objective sports data to test our theory. We did so because archival sports data allow the study of phenomena through natural experiments (Kahn, 2000), whereby issues of endogeneity are mitigated due to the level of control (Kocher, Lenz, & Sutter, 2012).…”
Section: Why Using Archival Sports Data For the Study Of Inter-organimentioning
confidence: 99%